User-Centric Harmonized Control for Single Joint Assistive Exoskeletons. (6th June 2016) - Haider, Usman; Nyoman, Indrawibawa I.; Coronado, Juan Lopez; Kim, Chanki; Virk, Gurvinder S.
The world is ageing and this poses a challenge to produce cost-effective solutions that can keep elderly people independent and active by assisting them in daily living activities. In this regard, this paper presents a new control method to provide physical assistance for any of the user joints (e.g., hip, knee, elbow, etc.) as needed by the wearer, by means of an assistive non-medical single joint exoskeleton with a "harmonized controller" capable of providing assistance in a natural way, and varying the assistance as needed by the user performing some activity. The control method is aimed at exoskeletons to provide assistance to users facing difficulty in any activity such as walking, sit-to-stand, etc., and, other than providing assistance as needed, it can also reduce the muscular effort for a completely healthy user. Harmonized control uses exoskeleton-integrated force sensors and motion sensors to identify the user's intentions and the assistance level required, generating appropriate control signals for the actuators by implementing a simple PID controller. To verify the proposed harmonized-control technique, simulations using MATLAB/SIMULINK were performed for a single joint system. An experimental test rig for a single joint was also developed using MATLAB Xpc Target for real-time control. User tests were also carried out for the knee joint and the results obtained from simulations, experimentation and user tests are reported and discussed here. The results achieved to date and reported here show harmonized control to be a promising user-centric solution for the development of single joint assistive exoskeletons for support as needed by the user in daily living activities.